2020
DOI: 10.3126/jcmc.v10i3.32042
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding family planning among the reproductive age women of Khopasi, Kavrepalanchowk

Abstract: Background: Uncontrolled population growth has been a problematic issue all over the world. Knowing the women’s and their husband’s knowledge and attitude towards family planning may help to intervene so that the practice can be increased. This might ensure the right of women to have child as they wish and later reduce unwanted pregnancies and abor­tions. Hence the present study is concerned with knowledge and attitude of women towards family planning. Methods: A cross-sectional study was conducted durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 6 publications
2
2
3
Order By: Relevance
“… 1 , 10 , 12 In contrast to our study where 27% of participants had a bachelor's or above level of education which was present in only 2.4% 10 and 4%. 12 …”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“… 1 , 10 , 12 In contrast to our study where 27% of participants had a bachelor's or above level of education which was present in only 2.4% 10 and 4%. 12 …”
Section: Discussioncontrasting
confidence: 90%
“…Regarding the permanent method of contraception, tubal ligation was done by about 9% of patients, similar to our study, it was 11.11 % 9 and 12.7% 12 in other studies. Vasectomy was practised by about 5.5% of participants in our study while it was found to be practised by 10.4% in another study done in Nepal.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations